Analysis of the effect of non-phacoemulsification cataract operation on corneal endothelial cell nucleus division - HuangZufeng; MaoXiaoqing (眼科学报, 2015)
Purpose: To investigate the effect of non-phacoemulsification cataract operation in two different patterns of nucleus delivery on the quantity and morphology of corneal endothelial cells and postoperative visual acuity. Methods: Forty patients diagnosed with cataract underwent cataract surgery and were assigned into the direct nuclear delivery and semi-nuclear delivery groups. Lens density was measured and divided into the hard and soft lenses according to Emery-little lens nucleus grading system. Non-phacoemulsification cataract operation was performed. At 3 d after surgery, the quantity and morphology of corneal endothelium were counted and observed under corneal endothelial microscope. During 3-month postoperative follow-up, the endothelial cell loss rate, morphological changes and visual acuity were compared among four groups. Results: Corneal endothelial cell loss rate in the direct delivery of hard nucleus group significantly differed from those in the other three groups before and 3 months after operation (P 0.05). Preoperative and postoperative 2-d visual acuity did not differ between the semi-delivery of hard nucleus and direct delivery of soft nucleus groups (P=0.49), significantly differed from those in the semi-delivery of soft nucleus (P=0.03) and direct delivery of hard nucleus groups (P=0.14). Visual acuity at postoperative four months did not differ among four groups (P=0.067). Conclusion: During non-phacoemulsification cataract surgery, direct delivery of hard nucleus caused severe injury to corneal endothelium and semi-delivery of soft nucleus yielded mild corneal endothelial injury. Slight corneal endothelial injury exerted no apparent effect upon visual acuity and corneal endothelial morphology at three months after surgery.